Biocompatible nanomaterials for targeted and controlled delivery of biomacromolecules - Kapoor, Deepak N; Dhawan, Sanju (New York, N. Y. : ASME, 2013)
Nanomaterials are organic or inorganic entities employed for the construction of various nanostructured devices or systems with nanometric dimensions. These nanostructures may include nanoparticles, nanowires, nanotubes, nanocapsules, nanocomposites as well as nanoporous solids. Nanomaterials have gained immense recognition, particularly in biomacromolecular delivery, owing to their capability of controlling the release rate or targeting the therapeutic moieties at molecular, cellular and organ level. Additionally, the problems of conformational and degradation stability associated with biomacromolecules like peptides, proteins, and genes have been addressed successfully by employing these nanomaterials. The degradation products of these biocompatible nanomaterials are non-toxic, non-immunogenic and easily resorbable by the regular physiological processes. The present chapter endeavors to describe the role of nanomaterials in the design, fabrication and development of various nanostructured, biomacromolecular delivery systems and devices. The chapter presents a discussion on various physicochemical properties, preparation techniques and analytical tools for characterizing these systems. The mechanisms of cellular internalization of nanomaterial based targeted systems are also discussed. Taking lead from various successful case studies, the present chapter provides a bird's eye view on the current advances in the field of nanomaterial based biomacromolecular delivery. A brief overview pertaining to the regulatory requirements and commercialization of these systems is also included. Various challenges posed during the development, scale up and large-scale production is also discussed. In a nutshell, besides, providing the salient details about the formulation and applications of biocompatible nanomaterials, the chapter would act as a ready reference for drug delivery scientists, device fabrication engineers and medical researchers working in this area.
12. Conclusions -- References.
Title from PDF t.p. (viewed on May 29, 2013).
Includes bibliographical references (p. 38-47) and index.
Keywords: Macromolecules; Nanostructured materials; Drug delivery systems; Nanomedicine; Nanostructures; Drug Delivery Systems; Nanomedicine; nanomaterials; engineering; organic; inorganic entities; biomacromolecular delivery; regulatory requirements; commercialization; biocompatible; Electronic books